Shockwave treated seed germination and physiological growth of Vigna mungo (L) in red soil environment. (January 2022) - Ramesh, R.; Vidhya, V.; Ali Khan, F. Liakath; Alnasrawi, Abeer Muhammed; Alkahtani, Jawaher; Elshikh, Mohamed S.; Kaviyarasu, K.
Abstract: In this study, the effect created using shock waves in the germination of the seedlings and growth aspects of the plant species Vigna mungo were investigated by studying agronomical traits, biochemical and phytochemical compounds. The test sample seeds were irradiated with shock waves with Mach numbers 1.7 and 2.2 through three shock pulses (5, 10 and 15 pulses) formed by the physically operated shock tube. After the shock wave treatment, the raw seeds and the shock pulse loaded seeds were sowed into the tested red soil at a simultaneous time and the physiological parameters like germination time, the height of the plant, shoot length, leaves count, branches produced, flower counts, and seeds produced from the plant were measured for every 5 days of by the POT analysis method. After 83 days of vegetation, the parts of the plants were harvested, and the specimens were analyzed using qualitative biochemical and phytochemical studies. The outcomes revealed that there is an increasing trend in the chlorophyll content of the shock - loaded seed samples over the control one. Similarly, there is an appreciable increasing trend in the phytochemicals was observed in the shock loaded seeds with comparison to the control. The study conducted by the application of shock pulses in the germination of seeds and improvement of the plant growth needs to be explored in the future with much more studies especially testing the hormonal changes produced by the shock in the seeds. Highlights: Shock wave was applied to stimulate the seed germination of Vigna mungo No fertilizer was used in this study Test sample seeds were irradiated with shock waves with Mach number 1.7 and 2.2 Chlorophyll content of the shock loaded seed samples over the control one Investigated by studying agronomical traits, biochemical & phytochemical compounds